Analysis of Locomotive Axle Load Transfer with Considerationof Adhesive Force Varying for Each Axle - WEI Jia-qi; ZHANG Kai-lin; YAO Yuan (机车电传动)
Considering the distribution of adhesive force varying with the axle load, the arithmetic of axle load transfer should beimproved. Taking a six-axis and a four-axis locomotive as cases respectively, arithmetic with considering and no considering adhesive forcedistribution was compared, the results of which showed that max wheel-set load-reducing ratio was different, and the former arithmeticreflected the real condition of the axle load transfer better. With the improved method, the optimum traction height of the both locomotiveswas optimized.